Characterizing and Developing Strategies for the Treatment of Community-Acquired Pneumonia at a Community Hospital - Mark C Fok; Zahra Kanji; Rajesh Mainra; Michael Boldt (Canadian Respiratory Journal)
BACKGROUND: Patients admitted to Lions Gate Hospital, North Vancouver, British Columbia, with a primary diagnosis of community-acquired pneumonia (CAP) have a mean length of stay (LOS) of 9.1 days compared with 7.9 days for peer group hospitals. This difference of 1.2 days results in an annual potential savings of 406 bed days and warranted an investigation into the management of CAP.